2018
DOI: 10.2147/ijn.s162836
|View full text |Cite
|
Sign up to set email alerts
|

A novel role in skeletal segment regeneration of extracellular vesicles released from periodontal-ligament stem cells

Abstract: PurposeThe combination of oral derived stem cells and 3-D scaffolds is considered advantageous in bone repair. In particular, collagen membranes possess ideal biological properties and can support infiltration and proliferation of osteoblasts, promoting bone regeneration. Our study aimed to develop a new biocompatible osteogenic construct composed of a commercially available collagen membrane (Evolution [Evo]), human periodontal-ligament stem cells (hPDLSCs) enriched with extracellular vesicles (EVs), or polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 59 publications
3
79
0
Order By: Relevance
“…Diomede et al showed that EVs derived from both hGMSCs and hPDLSCs, seeded on different scaffolds, in vitro, are able to promote the osteogenic differentiation of both hGMSCs and hPDLSCs. Specifically, EVs or polyethylenimine (PEI)-engineered EVs (PEI-EVs), in the presence of scaffolds, increased the osteogenic differentiation of hGMSCs and hPDLSCs as demonstrated by the increased gene expression of osteogenic markers, such as RUNX2 and BMP2/4 [49,50]. In detail, the increased gene expression of BMP2/4, found in this work is in accordance with our transcriptomic analysis and highlights the osteogenetic capacity of EVs.…”
Section: Discussionsupporting
confidence: 90%
“…Diomede et al showed that EVs derived from both hGMSCs and hPDLSCs, seeded on different scaffolds, in vitro, are able to promote the osteogenic differentiation of both hGMSCs and hPDLSCs. Specifically, EVs or polyethylenimine (PEI)-engineered EVs (PEI-EVs), in the presence of scaffolds, increased the osteogenic differentiation of hGMSCs and hPDLSCs as demonstrated by the increased gene expression of osteogenic markers, such as RUNX2 and BMP2/4 [49,50]. In detail, the increased gene expression of BMP2/4, found in this work is in accordance with our transcriptomic analysis and highlights the osteogenetic capacity of EVs.…”
Section: Discussionsupporting
confidence: 90%
“…A quantitative reverse-transcription polymerase chain reaction showed upregulation of osteogenic genes MMP-8, TGF-β1, TGF-β2, tuftelin-interacting protein (TFIP11), tuftelin 1 (TUFT1), RUNX2, SOX-9, and BMP2/4 in the presence of PEI-EVs. The increased expression of BMP-2/4 was confirmed for the collagen membrane loaded with PEI-EVs and human periodontal ligament MSCs both in vitro by Western blot and in vivo by immunofluorescence [194]. Ultimately, these results demonstrated that human periodontal ligament MSCs might be an effectual strategy in bone regenerative medicine, consequent to its potential to increase osteogenic and angiogenic mediators through the TGF-β-BMP signaling pathway.…”
Section: Periodontal Ligaments Mesenchymalmentioning
confidence: 65%
“…Dental MSC-CM promotes osteogenesis through enhancing the migration and mineralization potential of MSCs by TGF-β1 [153] as well as the upregulation of their osteoblastic and chondrogenic marker expression (Osterix, SOX-5, factor 8) [154]. In this context, TGF-β-BMP signaling pathway plays a pivot role in osseous regeneration induced by dental MSCs and their secretome through upregulating the expression of TGF-β1, TGF-β2, BMP2, BMP4, MMP8, TUFT1, TFIP11, RUNX2, and SOX-9 was detected [194], as well as VEGF, VEGFR2, and COL1A1 [193]. The osteoblastic differentiation potential is primarily mediated by TGF-βR1, SMAD1, BMP2, MAPK1, MAPK14, and RUNX2 through the TGF-β signaling pathway [177].…”
Section: Neuroprotective and Neurotrophic Effectsmentioning
confidence: 97%
“…The hDPSCs were fixed using 4% paraformaldehyde solution in sodium phosphate buffer (Lonza, Basel, Switzerland) [53,54]. The cells were permeabilized utilizing 0.5% Triton X-100 in PBS for 10 min followed by blocking with 5% skimmed milk in PBS for 30 min [55]; primary antibodies (anti-NFkB antibody, 1:250, Santa Cruz Biotechnology; anti-ERK antibody,1:200, Santa Cruz Biotechnology; anti-pERK antibody,1:200, Santa Cruz Biotechnology) were incubated for 2 h at room temperature.…”
Section: Immunohistochemistry and Confocal Laser Scanning Microscope mentioning
confidence: 99%